Horizons, paths and routes of the Sociology of Culture and the Sociology of Religions in Peru - Vega-Centeno B., Imelda (2020)
The subjects of religion and culture have been fundamental for the knowledge of Peru, even before its existence as a nation in the international context. These are not issues that put some theoretical frameworks or certain theories of interpretation of reality into “intellectual fashion”; socio-cultural and religious phenomena preceded them. It is in this long duration that we have to register the emergence of studies on religion and culture in the Andean populations. Retaking this long journey will allow us to locate the analytical and interpretive efforts, as well as the ethnological collections that took place for more than five hundred years, and in this way enrich our knowledge of the studied phenomena in order to place them within the interpretive scheme that allows locating to Peru as a nation.